Ambiguous Changes in Product Quality - Leffler, Keith B. (American Economic Review, 1982)
Economic goods are frequently sold according to a price per unit where the quantity characteristic does not measure all the economically important characteristics of the good. Milk is sold by the quart, automobiles rented by the mile, physicians' services bought by the visit, and tennis lessons by the hour. In all cases, heterogeneous units are available in the market and the price per unit quantity depends upon the amount of the unpriced characteristic contained in each unit. The per quart price of depends upon the butterfat content, the mileage costs of automobile rentals on the cars' make, and the price per unit time for personal services on the providers' skill and training. The common distinction made between these variants of the same good is that they differ in quality, where refers to the amounts of the unpriced attributes contained in each unit of the priced attribute.' Thus, is packaged according to the attribute milk liquid and the of refers to the ratio of butterfat per unit of liquid.2 This paper considers some of the unique aspects of the economics of supply and demand under this situation where products contain (at least) two desired attributes, only one of which is quantified and measured prior to purchase. Product is here defined by the ratio of the second quality attribute per unit of the measured quantity attribute.3 This simple specification of allows a direct link between standard economic models of related products and the economics of variable product quality. Previous analyses which treat simply as a shift parameter in the demand function are shown to obscure the actual subtleties of supply and demand with variable, endogenous quality.4 The paper proceeds by first examining the efficient and quantity, and the competitive equilibrium. The market equilibrium under monopoly is then contrasted in the second section. The general theme of the